The mixed effects of import barriers on humanitarian logistics - Kunz, Nathan (My University, 2014)
Through a multiple case study with four relief organizations, we analyze the impact of import barriers on humanitarian logistics. We find that these barriers negatively impact relief operations during the response phase, but may turn positive in the rehabilitation phase. This knowledge may help relief organizations improving their preparedness efforts.
, POMS 25th Annual Conference, Atlanta, GE, USA